Enhancing Public Legal Awareness and Compliance through a Legal Literacy Program - Dadi Waluyo; Sumardi (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2026)
Public legal awareness plays a fundamental role in promoting legal compliance, strengthening the rule of law, and fostering responsible civic participation. However, limited legal literacy remains a significant challenge, contributing to low levels of legal understanding, inadequate recognition of citizens' rights and obligations, and persistent non-compliance with legal regulations. This study aims to explore how a Legal Literacy Program enhances public legal awareness and encourages legal compliance within the community. The research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, participant observations, focus group discussions, and document analysis involving community members, legal practitioners, local government representatives, and program facilitators. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing, while data credibility was ensured through source triangulation, member checking, and prolonged engagement. The findings reveal that the Legal Literacy Program significantly improved participants' understanding of legal rights, obligations, and available legal remedies. The program also fostered positive changes in legal attitudes by encouraging respect for legal norms, increasing trust in formal legal institutions, and reducing reliance on informal dispute resolution practices that conflicted with statutory law. Furthermore, the participatory and context-based learning approach enabled participants to relate legal knowledge to everyday social issues, thereby strengthening legal awareness and voluntary legal compliance. The study concludes that legal literacy constitutes an effective community empowerment strategy for cultivating sustainable legal consciousness and promoting a culture of legal compliance. These findings provide practical implications for policymakers, educational institutions, and legal aid organizations in developing inclusive and community-oriented legal education programs to strengthen public access to justice and reinforce the implementation of the rule of law.